Do inter-continental playing styles exist? Using social network analysis to compare goals from the 2016 EURO and COPA football tournaments knock-out stages. (4th July 2017) - McLean, Scott; Salmon, Paul M.; Gorman, Adam D.; Naughton, Mitchell; Solomon, Colin
ABSTRACT: The current study applied social network analysis (SNA) to the passing networks leading to goals scored by successful teams during the knock-out stages of the 2016 European football championships (EURO) and COPA America football championships (COPA). The aim was to test SNA as a method for analysing the structure of passes leading to goals and to determine whether there were any differences between the passing networks associated with goals scored, by countries of the two different continents. The passes leading to goals during each tournament were represented as networks and analysed using SNA metrics. Additional analysis examined the duration of the networks, and location on the pitch in which the passing network originated and where the goals were scored from. No differences were found for all SNA metrics, network duration, and pitch locations between teams from the 2016 EURO and COPA tournaments. Despite previously reported differences in style between European football and football in the Americas, the findings indicate that the passing networks immediately prior to goals scored by teams from both continents are similar.